Clinical, FDG and amyloid PET imaging in posterior cortical atrophy - Singh, Tarun D. (J Neurol, 2015)
The purpose of this study was to identify the clinical, [(18)F]-fluorodeoxyglucose positron emission tomography (FDG-PET) and amyloid-PET findings in a large cohort of posterior cortical atrophy (PCA) patients, to examine the neural correlates of the classic features of PCA, and to better understand the features associated with early PCA. We prospectively recruited 25 patients who presented to the Mayo Clinic between March 2013 and August 2014 and met diagnostic criteria for PCA. All patients underwent a standardized set of tests and amyloid imaging with [(11)C] Pittsburg compound B (PiB). Seventeen (68 %) underwent FDG-PET scanning. We divided the cohort at the median disease duration of 4 years in order to assess clinical and FDG-PET correlates of early PCA (n = 13). The most common clinical features were simultanagnosia (92 %), dysgraphia (68 %), poly-mini-myoclonus (64 %) and oculomotor apraxia (56.5 %). On FDG-PET, hypometabolism was observed bilaterally in the lateral and medial parietal and occipital lobes. Simultanagnosia was associated with hypometabolism in the right occipital lobe and posterior cingulum, optic ataxia with hypometabolism in left occipital lobe, and oculomotor apraxia with hypometabolism in the left parietal lobe and posterior cingulate gyrus. All 25 PCA patients were amyloid positive. Simultanagnosia was the only feature present in 85 % of early PCA patients. The syndrome of PCA is associated with posterior hemisphere hypometabolism and with amyloid deposition. Many of the classic features of PCA show associated focal, but not widespread, areas of involvement of these posterior hemispheric regions. Simultanagnosia appears to be the most common and hence sensitive feature of early PCA.